Guru dalam Mencerdaskan siswa - Zainuddin Syarif (LP2M IAI Miftahul Ulum Pamekasan, 2015)
Learning is a communication of human’s existence that is othentic to be owned, continued and completed, the process of education should give a place to the insideout, process of self empowerment, based on the character paradigm and self motive.To achieve those all, the teachers are demanded to no only be able to transfer knowledge owned but inspire the students. The inspiring teachers will always give motivation and pattern modal to their students in order to face the era changes, inspiring teachers can design teaching methods well in order they have a compelling power, change, use for the sake of manage a more complete life paradigm concept